2020
DOI: 10.3390/ma13112597
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Copolymerization of Styrene Sulfide with Elemental Sulfur (S8)

Abstract: The superior ability of thiiranes (episulfides) to undergo ring-opening polymerization (ROP) in the presence of anionic initiators allows the preparation of chemically stable polysulfide homopolymers. Incorporation of elemental sulfur (S8) by copolymerization below the floor temperature of S8 permits the placement of a large quantity of sulfur atoms in the polysulfide mainchain. The utility of styrene sulfide (2-phenylthiirane; StS) for copolymerization with elemental sulfur is reported here. A few polysulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Poly(styrene-alt-sulphur), from S8/styrene sulphide ROCOP, showed that increasing the sulphur content (although not quantified) decreased the Tg from 58 to 43 °C which matched previous reports that increasing the sulphur wt% reduced brittleness. [203] It is emphasised that sulphur-sulphur bonds are often dynamic, a property exploited in autonomously self-healing polyurethane elastomers where macroscopic damage was healed through dynamic disulphides. [204] By simply bringing two ends of the cut specimen bar into contact mechanical properties were nearly completely restored after 24 h. In future, these ROCOP polymers should be explored as self-healing materials.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Poly(styrene-alt-sulphur), from S8/styrene sulphide ROCOP, showed that increasing the sulphur content (although not quantified) decreased the Tg from 58 to 43 °C which matched previous reports that increasing the sulphur wt% reduced brittleness. [203] It is emphasised that sulphur-sulphur bonds are often dynamic, a property exploited in autonomously self-healing polyurethane elastomers where macroscopic damage was healed through dynamic disulphides. [204] By simply bringing two ends of the cut specimen bar into contact mechanical properties were nearly completely restored after 24 h. In future, these ROCOP polymers should be explored as self-healing materials.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The Absorption band at 988 cm −1 was ascribed to the saccharide structure of chitosan [16] . A new band appeared at 657 cm −1 this band can be assigned to the stretching vibration of the C–S bond and this constitutes a successful synthesis of chitosan-SNPs formulation [21] . Figure 6 shows FTIR spectra of PEG-SNPs in which the absorption bands in the region 3450–3200 cm −1 with a peak at 3424.95 cm −1 were assigned to -OH stretching vibrations.…”
Section: Resultsmentioning
confidence: 74%
“…The developed protocols of sulfurization in the presence of fluoride anion can be of interest not only for the synthesis of sulfur-rich heterocycles, such as 1,2,4-trithiolanes [ 28 ], 1,2,4,5-tetrathianes [ 35 , 36 ] or 1,2,3,5,6-pentathiepanes, but also for the preparation of sulfur-rich polymers starting with alkyl- [ 37 , 38 ] or aryl [ 39 ] substituted thiiranes. In the present work, fluoride anion was shown to act as an alternative, nucleophilic catalyst and can replace smelly and unstable sodium (or potassium) thiophenolate in the activation of elemental sulfur in reactions with thiiranes.…”
Section: Discussionmentioning
confidence: 99%